PENGARUH MEDIA PEMBELAJARAN DIGITAL TERHADAP KETERAMPILAN MENGAJAR GURU KELAS IV DI SEKOLAH DASAR - Fadhilah nurdin; Adrias Adrias; Aissy Putri Zulkarnaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of the use of digital learning media on the teaching skills of grade IV teachers at Pariaman City State Elementary School. Digital learning media is expected to improve the effectiveness and quality of teaching, especially in improving teachers' teaching skills. The method used in this study is a quantitative approach. The sample of this study consists of 1 grade IV teacher in several elementary schools in Pariaman City who use digital learning media in teaching and learning activities. Data was collected through observation, and questionnaires filled out by teachers and students. The results of the analysis showed that the use of digital learning media significantly increased teachers' teaching skills, both in terms of delivering materials, using varied methods, and in increasing interaction with students. The results of this research are expected to be a reference in the development of the use of digital learning media to improve the quality of teaching at the elementary school level, especially in Pariaman City. Thus, the integration of technology in learning is an important step in creating a more effective and efficient education.